Angular dependencies of Cerenkov-light in water for carbon-ion, high energy x-ray and electron. (18th February 2019) - Hirano, Yoshiyuki; Yamamoto, Seiichi
Abstract: Because Cerenkov light is emitted above the threshold energy of the electrons (∼260 keV) in water and is emitted to forward directions, the light intensity distributions are different from the dose for x-ray and electron from LINAC. Cerenkov-light component was also observed with the depth profiles in carbon-ion. However the angular dependencies of the Cerenkov-light distributions were not obvious. Thus we calculated the depth profiles of the produced light distributions for 240 MeV n −1 carbon-ion, 6 MV x-ray, and 9 MeV electrons using Monte Carlo simulation. After we confirmed the simulation accuracies by comparing with the measured results, we calculated the depth profiles of luminescence of water and Cerenkov-light with various angles for these three types of radiations. With the simulation results, it became obvious that the depth profiles were significantly different with the angles for the produced light containing the Cerenkov-light. Cerenkov-light components were much higher at the larger angles. We also found the almost identical depth profile to dose with the angle of 10 degree to the right angle of the beam direction for 6 MV x-ray.